Estágios imaturos de Lepidoptera e seus parasitoides associados ao gênero Myrsine L. (Primulaceae) na Reserva Biológica da Serra do Japi, Jundiaí, São Paulo - Barbosa, Anderson Henrique da Silva (2025)
Changes in rainfall can affect the structure of ecological communities, influencing the interactions amongst trophic levels. In terrestrial tritrophic systems involving herbivores such as immature Lepidoptera, their host plants and parasitoids, these changes are very complex and hard to predict, especially in the tropical Atlantic rainforest. Since the knowledge about species distribution and seasonal patterns are necessary for conservation efforts, the main objective of this work is to evaluate the temporal variation in the community structure of immature Lepidoptera associated with Myrsine L. species and their interactions with parasitoids in an atlantic rainforest area. The study was conducted at the Reserva Biologica da Serra do Japi, in the township of Jundiaí, São Paulo state, Brazil. From March to August 2024, Immature Lepidoptera were sampled with an entomological umbrella in 33 host plants, distributed in two species of the family Primulaceae: Myrsine umbellata (N=19) and Myrsine gardneriana (N=14). The immature lepidopterans were taken to the Instituto Nacional de Ciência e Tecnologia dos Hymenoptera Parasitoides (INCT-HYMPAR) in the town of São Carlos, SP, and were kept under laboratory conditions until the emergence of Adult Lepidoptera or eventual parasitoids. The specimens were deposited at the Coleção Taxonômica do Departamento de Ecologia e Biologia Evolutiva, Universidade Federal de São Carlos, Brazil (DCBU). In total, 215 larvae of Lepidoptera were recorded, distributed in 8 families (Erebidae, Geometridae, Limacodidae, Noctuidae, Psychidae, Riodinidae, Saturniidae and Tortricidae) and 46 species and morphospecies. Phrygionis polita was the most abundant species (N=46). Richness and Diversity values were higher for the dry season and the early dry season had the higher sample coverage. Immature abundance was statistically consistent over time (p=0,86084). There was a significant variation in the species composition (p=0.0116) and the variation was mostly explained by the higher abundances of some species in the early dry season. A total of 131 parasitoids were reared, belonging to two orders (Hymenoptera and Diptera), 4 families and 19 morphospecies. A new species of the genus Colpotrochia Holmgren was recorded and described. Parasitism proportion differed between seasons and was higher in the dry season; changes in the trophic interactions were also observed. Thus, this work provides new ecological data and reinforces the importance of studies with immature Lepidoptera for conservation.